Desain Dan Perancangan Multi Channel Analyzer (Mca) Dengan 16 Input 4096 Kanal memori berbasis komputer pribadi dan sistem telemonitoring - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The aim of this research is to set up a sufficient .system. which is used for a real-time Multi Channel Analyzer (MCA) with 16 inputs and 4096 remote channels based on a personal computer and a telernonitoring system. The completed research results in the hardware design of a multi channel analyzer (MCA) with 16 inputs and 4096 memory channels based on a personal computer. The MCA contains buffer analog series, a multiplexer, an ADC, a parallel port interface, and a power supply. Several tests were done step by step on each series, and then continued by an overall lest. The test result shows that the MCA can tramfer a I2-hit data SillMillancoffsly through the parallel port and can accommodate input voltage of Cl to 10 V The MCA has 230 la dead time, so if MaXiInfiln decay that could still be detected are 240,000 cpm. IN!, test results 012 % prove can convert pulses with constant height into the appropriate digital values. DNL test results 1,486 %. The experiment concludes that the MCA was capable to inform the channel number. A Radio FM can transfer data through radio frequency with operational frequency 'UHF FM 937 MHz.